Type 2 Diabetes TBL for M1 Students - Satoru Nishimoto; William Brescia; Russell Chesney; Vicki Park; Melburn Park; Sunil Sinha; Robert Ferry (Association of American Medical Colleges, 2014)
Abstract Introduction This team-based learning (TBL) session examines the impact of type 2 diabetes (T2D) on energy metabolism as covered in first-year basic sciences for medical students. Knowledge of molecular mechanisms in energy metabolism and signal transduction are required. Knowledge of anatomy is integrated to apply anatomical knowledge to T2D. This TBL is intended to take place subsequent to carbohydrate metabolism and abdominal anatomy to reinforce knowledge of these subjects. Methods This TBL includes a readiness assurance test (RAT) and a worksheet that applies basic science knowledge to medical decision making. In addition, there are prereading assignments to provide learners with information on genetics and nutrition. Each of our TBL sessions consists of 84 students in permanent six-person teams plus several faculty facilitators. As an interdisciplinary TBL, the module is facilitated by a medical education professional for the RAT events and teams of basic scientists and clinicians for the application. The RAT assessments are completed within 30 minutes, with the rest of the time devoted to the clinical case and the application questions. A PowerPoint/TurningPoint presentation and a Turning Technologies Response System captures individual RAT (iRAT) responses, and printed sheets and scratch-off Immediate Feedback Assessment Technique (IF-AT) cards capture team RAT (tRAT) responses. These are graded for the course. Teams have cards, and stands are present on team tables for application response simultaneous reveals. The application exercise is not graded or recorded. Results This TBL has been implemented for three entering M1 classes in the first (fall) semester. The results of the RAT overall are consistent from year-to-year. The iRAT scores have steadily increased while the tRAT scores have consistently remained high. Students vote each year on what percentage of their RAT score comes from the iRAT as compared to the tRAT, and each year they have chosen the highest percentage of their score allowed to come from the tRAT (75%), with the iRAT counting 25% of the TBL score. Discussion In this molecular course, TBL has proven to be a flexible active learning experience for M1 students. The curriculum has evolved over the 3 years of implementation, and questions in the RAT and Applications have been changed as part of this process with continued change being likely. The faculty facilitators must be able to respond by updating the content in the TBL as curriculum content and delivery of content evolves.